Learning Strategies Using Flash Player in Motorcycle Engineering Lessons to Realize Ease of Learning in Class - Heri Majid (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
One of the goals of national education as stated in law number 20 of 2003 is that the main goal that must be an orientation in education is to educate the life of the nation and develop the whole human being, namely people who believe and fear God Almighty and have high morals. Motorcycle automotive engineering subject matter is a lesson that emphasizes the skills and expertise of students about motorcycle vehicles. In general, the objective of the Motorcycle Engineering Skills Competency (TSM) refers to the contents of the National Education System Law (UU SPN) article 3 concerning National Education Goals and the elucidation of article 15 which states that vocational education is secondary education that prepares students especially to work in the field of certain. In particular, the Motorcycle Engineering Skills Competency aims to equip students with the skills, knowledge and attitude to be competent in the maintenance, maintenance and repair of motorcycles (engine, power converter, chassis and electricity on motorcycles).